SIFAT PAPAN WOL KAYU DARI 8 JENIS KAYU MALUKU UTARA - I M Sulastiningsih; Paribotro Sutigno; M l Iskandar (Pusat Penelitian dan Pengembangan Hasil Hutan, 1995)
The result of laboratory test of wood-wool board properties manufactured from 8 individual wood species obtained from North Maluku are reported in this paper. The tests comprising board density, moisture content, thickness reduction due to compression, and bending strength.The study reveals that the average yield of wood-wool is 492. 75 kg/m3 of log input. The wood-wool of Parinari corymbosa, Shorea koordersii, Hopea sp. and Horsfieldia sylvestris must be soaked in cold water for 24 hours prior to wood-wool board manufacture, while the otherfour species do not require the soaking. The physical and mechanical properties of wood- wool board from seven wood species mineralized with Ca CJ 2 are in comformity with the DIN 1 101 standard. Only six wood species, however, mineralized with Ca(OH)2 suspension meet the standard requirement. The identical commercial name of wood not necessarily produce a comparable quality board. Apart from the species, growth and environmental factors are believed to contributing to board properties.